2010
DOI: 10.1097/dad.0b013e3181cb3fbe
|View full text |Cite
|
Sign up to set email alerts
|

Early Histopathologic Changes in Grover Disease

Abstract: These findings may represent a diagnostic clue in cases of early Grover disease, if clinical correlation is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…We found minimal inflammation in our DD cases, which can be a helpful feature in distinguishing it from Grover disease. Eosinophils are common in Grover disease (approximately 80% of cases), although they are often present in small numbers . While eosinophils are frequently found in the dermis in Grover disease, we also found eosinophils throughout the epidermis in approximately 20% of cases and intraepidermal neutrophils in about 15%.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…We found minimal inflammation in our DD cases, which can be a helpful feature in distinguishing it from Grover disease. Eosinophils are common in Grover disease (approximately 80% of cases), although they are often present in small numbers . While eosinophils are frequently found in the dermis in Grover disease, we also found eosinophils throughout the epidermis in approximately 20% of cases and intraepidermal neutrophils in about 15%.…”
Section: Discussionmentioning
confidence: 47%
“…Eosinophils are common in Grover disease (approximately 80% of cases), although they are often present in small numbers. 3,21,23,[32][33][34][35] While eosinophils are frequently found in the dermis in Grover disease, we also found eosinophils throughout the epidermis in approximately 20% of cases and intraepidermal neutrophils in about 15%. PRP is regarded as a pauci-inflammatory dermatosis, although eosinophilic infiltrates and lichenoid infiltrates have been reported.…”
Section: Inflammatory Infiltratesmentioning
confidence: 80%
“…According to this study, a vascular degeneration in the form of endothelial tumefaction due to cytoplasmic edema and erythrocyte extravasation can often be found [6]. Other researchers showed that early histological lesions in Grover's disease are represented by elongation of rete ridges, mild focal acantholysis and occurrence of eosinophils, which can be helpful in dermatopathological analysis of discrete nonspecific lesions if the clinical correlation is feasible [7].…”
Section: Discussionmentioning
confidence: 67%
“…Στις περιπτώσεις αυτές, πρώιμα ιστοπαθολογικά στοιχεία της πάθησης θεωρούνται η επιμήκυνση των επιδερμιδικών καταδύσεων σε συνδυασμό με εστιακή ακανθόλυση και παρουσία ηωσινοφίλων στο χόριο. 165 Συνήθως, η επιδερμίδα εμφανίζει ακανθόλυση και ενδοεπιδερμιδικές φυσαλίδες με υπερκείμενη υπερκεράτωση και παρακεράτωση. Μπορεί επίσης να υπάρχει εναλλασσόμενη ορθοκεράτωση-παρακεράτωση.…”
Section: ) σπογγιωτική δερματίτιδαunclassified
“…Σε μεγάλο αριθμό περιστατικών παρατηρήθηκε διαφόρου βαθμού υπερκεράτωση ενώ παρακεράτωση στο 70% των περιπτώσεων (ν=77). Σε αντίθεση με τους Melwani και συνεργάτες 165 δεν διαπιστώσαμε επιμήκυνση των επιδερμιδικών καταδύσεων ως πρώιμο και σταθερό εύρημα σε όλα τα περιστατικά μας.…”
Section: συζητησηunclassified